KARAKTERISTIK MEKANIK ALUMINIUM PADUAN HASIL KOMPARASI PROSES EQUAL CHANNEL ANGULAR PRESSING VS ROLLING: Severe Plastic Deformation (S.P.D) - Pramono, Agus; Alhamidi , Ahmad A.; Firmansyah, Asep A.; Suryana, Suryana; Alfirano, Alfirano; Ridwan, Asep (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Aluminum alloys are vital in industries such as automotive, aerospace, and manufacturing due to their strength, lightweight, and corrosion resistance. To enhance their mechanical performance and energy efficiency, advanced methods like severe plastic deformation (SPD) have been explored, with equal channel angular pressing (ECAP) proving effective in refining grain structures and improving material properties. ECAP was applied to the AA5XXX series aluminum alloy using a fixed-section die with a mold groove angle of 105° and a curve angle of 75º, while keeping the cross-sectional dimensions of the specimen constant. Route C was employed, involving a variable number of passes. Subsequently, the results of the ECAP process were further enhanced through a 50% reduction roll process. A significant increase in strength and hardness was observed when comparing the combination of ECAP and 50% rolling with ECAP alone. The mechanical properties increased by 58.11% for the first pass, 58.66% for the second pass, 58.92% for the third pass, and 59.19% for the fourth pass. Grain refinement also exhibited substantial improvement in this combined process, with increases of 68.18% for the first pass, 77.59% for the second pass, 85.71% for the third pass, and 87.38% for the fourth pass. Pure ECAP yielded a maximum strength of 251 MPa and a hardness of 78.43 HB, while the combination of ECAP with 50% rolling achieved a maximum strength of 277 MPa and a hardness of 86.17 HB. This research successfully increased tensile strength and hardness while altering the microstructure grain size morphology.